MEMBANGUN MODEL PEMBELAJARAN BERBASIS KONTEKSTUAL (CTL) DALAM PENDIDIKAN KARAKTER SISWA SD DI KOTA MEDAN. - Sorta Simanjuntak (JURNAL PENELITIAN BIDANG PENDIDIKAN, 2012)
The research objective is to build: 1) the model of studing the basic ofCTL the character education for primary students; 2) to know about the  competenceof  teacher to build and implementation of  CTL in  learning; 3) to know about theconstribution of  CTL in  learning  the character build  for primary  students; 4) toknow about the process learning with CTL learning in education of primarystudents  in Medan. This study uses the  "Research and Development R & D Cycle.The population research of primary  teacher in Medan. And the sample  who theteacher  in the village of Medan city. The data are collection techniques used areanquet with Likert’s scale, observation, and  documentation. The analysis of data aredescription of statistic and the interpretation of normative scale. The result of theanalysis data are : 1) building  of the teacher’s competence of model CTL in thelesson plan is better in the value 3,01; 2) the value of  anquet about the concepsionalof teacher  2,82 with category good; and 3) the observation about how the teacher toteach is value 2,49 in category not bad. The conclution  of the design learn of CTLmodel’s with description is good determinat. Mean while the implementationshowed that all are not good yet.